Executive Committee Minutes 2008-02-28 - Academic Senate:::::::::
Resolution on the Collegiate Learning Assessment, Process of Transforming Course Design discussion, Ad-Hoc Committee resolution on CIHS and correspondence from former managers of CIHS, Economics and Music Revisions, Constitutional Amendment for faculty referenda, Resolution re: Staffing Ratios for Student Counseling and Psychological Services, Handouts at the Senate, AS decision to leave CSSA and support for Northern Illinois University